The coordinated regulatory impact of AcsS and TpdA on biofilm formation in Vibrio parahaemolyticus - Ni, Bin; Chang, Jingyang; Zhou, Yining; Li, Wanpeng; Tian, Zhukang; Lu, Renfei; Zhang, Yiquan (Frontiers in Microbiology, 2025)
Vibrio parahaemolyticus, a marine pathogen, employs biofilm formation to enhance environmental persistence and transmission. Biofilm development is intricately regulated by cyclic di-GMP (c-di-GMP), whose levels are controlled by diguanylate cyclases (DGCs) and phosphodiesterases (PDEs). This study elucidates the coordinated regulatory roles of the LysR-type transcriptional regulator AcsS and the PDE TpdA in biofilm formation. Through genetic, transcriptomic, and biochemical analyses, we demonstrate that AcsS promotes biofilm formation by directly activating the exopolysaccharide biosynthesis gene cpsA and indirectly repressing tpdA, a gene encoding a c-di-GMP-degrading enzyme. Conversely, TpdA inhibits acsS expression and antagonizes cpsA transcription. RNA-seq revealed that AcsS globally regulates 235 genes, including those linked to flagella, type IV pili, and capsular polysaccharides. Intracellular c-di-GMP quantification showed that AcsS elevates c-di-GMP levels, while TpdA reduces them, establishing a feedback loop. Phenotypic assays confirmed that AcsS-dependent biofilm enhancement operates independently of TpdA, though TpdA partially suppresses biofilm formation in the absence of AcsS. These findings unveil a regulatory circuit where AcsS and TpdA coordinately modulate c-di-GMP metabolism and biofilm-associated gene expression, highlighting them as promising targets for disrupting biofilm-mediated persistence and transmission of V. parahaemolyticus.